A moving bead on a rotating rod - Pipinos, Savas (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
We present a cross thematic activity in the fields of physics and mathematics. This is part of a series of three activities in which students are guided to conjecture or discover the behaviour of physical models and express physical laws using mathematics from their school curriculum. They use The Geometer’s Sketchpad dynamic geometry environment to simulate, verify and utilize their results or to hypothesise on the theoretical properties of a moving bead on a rotating rod. A thematic design triangle that takes into consideration the two basic axes of computer supported collaborative learning and the notion of a scientific model was used for the cross thematic approach.